Pharmacogenetic Predictors of Statin-Mediated Low-Density Lipoprotein Cholesterol Reduction and Dose Response - Voora, Deepak (2008)
BACKGROUND: There is interindividual variation in low-density lipoprotein cholesterol (LDLc) lowering by statins and limited study into the genetic associations of the dose dependant LDLc lowering by statins. METHODS AND RESULTS: Five hundred nine patients with hyperlipidemia were randomly assigned atorvastatin 10 mg, simvastatin 20 mg, or pravastatin 10 mg (low-dose phase) followed by 80 mg, 80 mg, and 40 mg (high-dose phase), respectively. Thirty-one genes in statin, cholesterol, and lipoprotein metabolism were sequenced and 489 single nucleotide polymorphisms with minor allele frequencies >2% were tested for associations with percentage LDLc lowering at low doses using multivariable adjusted general linear regression. Significant associations from the analysis at low dose were then repeated at high-dose statins. At low doses, only 1 single nucleotide polymorphism met our experiment-wide significance level, ABCA1 rs12003906. Twenty-six subjects carried the minor allele of rs12003906, which was associated with an attenuated LDLc reduction (LDLc reduction in carriers versus noncarriers −24.1±2.6% versus −32.2±1.5%; P=0.0001). In addition, we replicated the association with the APOE ε3 allele and a reduced LDLc reduction. At high doses, carriers of the minor allele of ABCA1 rs12003906 and the APOE ε3 allele improved their LDLc reduction but continued to have a diminished LDLc reduction compared with noncarriers (−30.5±4.0% versus −42.0±2.4%; P=0.005) and (−38.5±1.9% versus −45.3±2.8%; P=0.009), respectively. CONCLUSIONS: An intronic single nucleotide polymorphism in ABCA1 and the APOE ε3 allele are associated with reduced LDLc lowering by statins and identify individuals who may be resistant to maximal LDLc lowering by statins.